1971
DOI: 10.1021/jo00807a010
|View full text |Cite
|
Sign up to set email alerts
|

Thermal rearrangement of O-(2-pyridyl)oximes

Abstract: The experiment was repeated using the procedure outlined (19) R. C. Weast, Ed., "Handbook of Chemistry and Physics," 49th ed, Chemical Rubber Publishing Co., Cleveland, Ohio, 1968, p C520. above except the reactants were refluxed in 100 ml of ethanol to give 1.80 g (35%) of 4 and 5.3 g of crude 9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 6 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…75 This process becomes dominant for formation of the 2-pyridone derivatives 97. 82 Milder reaction conditions (HCl in acetic acid at 20−25 °C) allows in some cases isolation of the imine salts 94. 67,83 Side processes arising from the initial oxime ether 93 undergoing hydrolysis 84 or other migrations 75 have also been reported.…”
Section: [13]-rearrangement Of Bis(oxy)enamine-based Oxyanionsmentioning
confidence: 99%
“…75 This process becomes dominant for formation of the 2-pyridone derivatives 97. 82 Milder reaction conditions (HCl in acetic acid at 20−25 °C) allows in some cases isolation of the imine salts 94. 67,83 Side processes arising from the initial oxime ether 93 undergoing hydrolysis 84 or other migrations 75 have also been reported.…”
Section: [13]-rearrangement Of Bis(oxy)enamine-based Oxyanionsmentioning
confidence: 99%
“…In 1970 Sheradsky demonstrated that the O -vinyl oxime derived from the addition of acetophenone oxime to dimethylacetylene dicarboxylate can be thermally rearranged to the corresponding pyrrole. , This synthetic approach was further developed by Trofimov who showed that variously substituted pyrroles could be obtained from ketoximes and unactivated alkynes under superbasic conditions . Although the Trofimov reaction is limited by the harsh reaction conditions, the lack of regioselectivity and poor performance observed for substituted alkynes, it has been successfully applied in a number of pyrrole syntheses. , Recently, Camp and co-workers have developed procedures that provide access to pyrroles with EWG-groups, that are not accessible under classical Trofimov reaction conditions, via nucleophilic catalysis and gold-multifaceted catalysis approach. …”
Section: Introductionmentioning
confidence: 99%